Nanometer CMOS Sigma-Delta Modulators for Software Defined Radio - Morgado, Alonso; del Río, Rocío; de la Rosa, José M. (Springer New York : Imprint: Springer, 2012)
This book presents innovative solutions for the implementation of Sigma-Delta Modulation (SDM) based Analog-to-Digital Conversion (ADC), required for the next generation of wireless hand-held terminals. These devices will be based on the so-called multistandard transceiver chipsets, integrated in nanometer CMOS technologies. One of the most challenging and critical parts in such transceivers is the analog-digital interface, because of the assorted signal bandwidths and dynamic ranges that can be required to handle the A/D conversion for several operation modes.   This book describes new adaptive and reconfigurable SDM ADC topologies, circuit strategies and synthesis methods, specially suited for multi-standard wireless telecom systems and future Software-defined-radios (SDRs) integrated in nanoscale CMOS. It is a practical book, going from basic concepts to the frontiers of SDM architectures and circuit implementations, which are explained in a didactical and systematic way. It gives a comprehensive overview of the state-of-the-art performance, challenges and practical solutions, providing the necessary insight to implement successful design, through an efficient design and synthesis methodology.  Readers will learn a number of practical skills - from system-level design to experimental measurements and testing. Provides tutorial presentation of innovative SDM-based solutions for the next generation of wireless telecom systems; Presents a systematic design methodology, based on the combined use of optimization and behavioral simulation; Gives practical guidelines on the architecture selection, sizing, and electrical implementation of several SD ICs integrated in nanometer CMOS; Provides readers with a comprehensive overview of the basics, state-of-the-art performance, applications, challenges and solutions.